3rd International Conference on Fuel Cell Science, Engineering and Technology 2005
DOI: 10.1115/fuelcell2005-74078
|View full text |Cite
|
Sign up to set email alerts
|

Stresses in Proton Exchange Membranes Due to Hydration-Dehydration Cycles

Abstract: Durability of the proton exchange membranes (PEM) is a major technical barrier to the economic viability of stationary and transportation applications of PEM fuel cells. In order to reach Department of Energy objectives for automotive PEM fuel cells, a design lifetime of 5,000 hours over a wide temperature range is required. Reaching these lifetimes is an extremely challenging technical problem. Though good progress has been made in recent years, there are still issues that need to be addressed to assure succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This is an extension of previous work [13,14], where only the elastic behavior of the membrane was considered. An uncoupled theory is assumed, for which the addi tional temperature changes brought by the strain are neglected.…”
Section: Theory For Isotropic Elasto-plasticitymentioning
confidence: 65%
See 1 more Smart Citation
“…This is an extension of previous work [13,14], where only the elastic behavior of the membrane was considered. An uncoupled theory is assumed, for which the addi tional temperature changes brought by the strain are neglected.…”
Section: Theory For Isotropic Elasto-plasticitymentioning
confidence: 65%
“…The model used in the current investigation is an extension of a model developed in previous studies [13,14]. In the cur rent work, we incorporate temperature and humidity dependent properties of the PEM, as well as including plasticity and inves tigating the response to one simplified duty cycle.…”
Section: Assumptionsmentioning
confidence: 99%
“…The cases where the grooves are aligned will be referred to as "aligned" and the nonaligned cases as "alternating." Our previous study [21] showed that the magnitudes of the stresses in the membrane are much higher than that in GDEs or the plates. Also, the mismatches in the thermal and swelling coefficients lead to compression in the membrane and bending in the GDE.…”
Section: Introductionmentioning
confidence: 99%
“…From our ongoing research, the dimensional change of NAFION® from 35% to 100% relative humidity at 85° C is approximately 15%. The units of f we used in the model are mm/mm per percent relative humidity change, giving the swelling coefficient for NAFION® as 2300 (10 −6 mm/ mm per percent relative humidity change) [21].…”
Section: Introductionmentioning
confidence: 99%
“…thermal barrier coatings [1 -3]), humidity (e.g. fuel cells [4], silica gtass [5]). and environ mental attacks (e.g.…”
Section: Introductionmentioning
confidence: 99%